Catalogue of mutations in Mycobacterium tuberculosis complex and their association with drug resistance - Rodwell, T; Miotto, P; Köser, C; Walker, T; Fowler, PW; Knaggs, J; Iqbal, Z; Hunt, M; Chindelevitch, L; Farhat, M; Cirillo, D; Crook, D; et al. (World Health Organization, 2021)
Of the 10 million people estimated to have fallen ill with tuberculosis (TB) in 2019, nearly half million developed TB resistant to rifampicin (RIF), and over one million developed TB susceptible to RIF but resistant to isoniazid (INH). Drug resistance must be detected rapidly and accurately to initiate appropriate and effective treatment.